Behind the Door Remains the Custom: Adapting Dwellings for New and Old Inhabitans in Late 15th-Century Malaga - Cruces Blanco, Esther (De Medio Aevo, 2026)
At the end of XV century, Málaga and its land is a frontier city whose neighbours, winners and defeated of the long war of Granada, had to adapt their way of life, the ítems they use and the houses where they live to different cultural traditions but known to both parties; anyone has to comply obligations and prohibitions impelled by the Castillian Crown. Old christians, foreigners, jews, mudejars and moorishs made exhibition of objects, furnitures and clothing, at the same time as they were concealed and hiden both at the public and at the private área. Behind the door of each home arised new ways of living together but also old ways to survive. A complex society in a world of relevants geopolitical, social and thinking changes. Records provide a glimpse of this fact and they are explicits when those ítems adopted and adapted are vehicles for the exhibition; those who need to write down facts and actions  were cautious when it was a risk, it was a very difficult balance.
Keywords: Adapted items; concealment; exhibition; frontier; Málaga; objects